How polymer particles delay the OPC hydration: evaluating the impact of adsorption and complexation - Schreiber, Jakob; Kong, Xiangming; Jansen, Daniel (Materials and Structures, 2026)
The retardation and depression mechanisms induced by two differently charged styrene acrylate copolymer latexes on OPC hydration, adsorption and complexation, were investigated. The used latexes were dialysed latexes where the constituents beside the polymer particles were removed and a high polymer/cement ratio was used to ensure that complexation might occur. For the first time ion complexation by polymer particles was observed directly by measuring ions in unfiltered pore solutions. The results were compared with the filtered pore solution composition, total organic carbon content, in-situ X-ray analysis and heat flow calorimetry. It is found that complexation occurs, but the effect on the hydration is limited compared to the adsorption of polymer particles. The adsorption process, dependent on the surface charge of the polymer particles, determines the strength of the negative influence on the early OPC hydration.
CRIS-Team Scopus Importer:2026-01-26
Keywords: Adsorption; Hydration; Polymers; Portland cement; Retardation